Perancangan Website Penjualan di Pet Shop Puffy Juwana Menggunakan Framework Laravel - Hebertus Tanuwidjaja; Ramos Somya (LPPM STIKOM Tunas Bangsa, 2023)
The sales system at Puffy Petshop is currently ineffective in conducting sales. This is due to a lack of promotion and information at Puffy Petshop. This research aims to design a dedicated e-commerce application for Puffy Petshop to enhance the online shopping experience for pet products. The research involves analyzing user needs, designing an attractive user interface, develop ping innovative features, and implementing a prototype application. The research methods employed include surveys and interviews with Puffy Petshop owners to identify user needs. The outcome of this research is a prototype of the Puffy Petshop e-commerce application, which includes key features such as product search, online ordering, secure payment, order status notifications, customer reviews, and account management. The prototype application is then tested for functionality and usability through functional testing and user testing to ensure optimal performance and usefulness. In this study, a website design for sales at Puffy Petshop in Juwana will be created using the Laravel Framework. The implementation of this sales website is expected to address the existing issues at Puffy Petshop in Juwana.